2013
DOI: 10.1590/s0103-84782013001200016
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of (co)variance components and genetic parameters for growth traits in Suffolk lambs

Abstract: RESUMO Objetivou-se estimar os componentes de (co) variância e herdabilidades para pesos ao nascer (PN), à desmama (PD) e aos 180 dias de idade (P180), além dos ganhos médios diários de peso do nascimento à desmama (GMD N-D ), do nascimento aos 180 dias de idade (GMD N-180 ) e da desmama aos 180 dias de idade (GMD D-180

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
(20 reference statements)
2
5
0
1
Order By: Relevance
“…Based on the most appropriate models, direct heritability increased whereas maternal heritability decreased with increasing lamb age. Similar estimates of direct and maternal heritability were reported in Polypay (Hanford et al, 2006) and NSIP Suffolk lambs (Notter, 1998), but lower estimates were reported for Suffolk (Tamioso et al, 2013), NSIP Targhee (Notter and Hough, 1997), and NSIP Polypay lambs (Notter, 1998). Ratios of maternal heritability to direct heritability decreased with age, from 94% for BWT to 30% for PWWT, and were consistent with results summarized by Safari et al (2005).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Based on the most appropriate models, direct heritability increased whereas maternal heritability decreased with increasing lamb age. Similar estimates of direct and maternal heritability were reported in Polypay (Hanford et al, 2006) and NSIP Suffolk lambs (Notter, 1998), but lower estimates were reported for Suffolk (Tamioso et al, 2013), NSIP Targhee (Notter and Hough, 1997), and NSIP Polypay lambs (Notter, 1998). Ratios of maternal heritability to direct heritability decreased with age, from 94% for BWT to 30% for PWWT, and were consistent with results summarized by Safari et al (2005).…”
Section: Discussionsupporting
confidence: 82%
“…Proper interpretation of parameter estimates derived from animal models for traits influenced by maternal effects depends on both the structure of the data and the model used for the analysis (Safari et al, 2005). Studies on various sheep breeds have shown important maternal effect on lamb BW (Lewis and Beatson, 1999;Bromley et al, 2000;Wilson et al, 2005;Koyuncu and Duru, 2009;Tamioso et al, 2013;Everett-Hincks et al, 2014). The significant (P < 0.05) maternal effects on BW in these Katahdin lambs show that failure to properly account for maternal effects leads to overestimation of heritability and may result in unrealistic expectations for improvement of additive breeding values.…”
Section: Discussionmentioning
confidence: 99%
“…Santana et al (2013) obtained similar results in an evaluation of various models in the same population of sheep, but using fewer data. In addition, Mohammadi et al (2015) reported similar results in Lori sheep and Tamioso et al (2013) in Suffolk sheep (BW, 0.17), as did Hanford et al (2003) and Gowane et al (2015) for WW (0.11 and 0.15, respectively), and Eler et al (1995) for BW (0.12) and WW (0.13) in Nelore cattle.…”
Section: (Co)variance Components and Genetic Parameterssupporting
confidence: 51%
“…However, these data are not in agreement with those of Mohammadi et al (2015), who reported low values in Lori sheep this discrepancy could be due to environmental effects. Other studies have also reported low to moderate values for weight gain at weaning and post-weaning of 0.07 and 0.22, respectively (Magalhães et al, 2013;Tamioso et al, 2013;Oliveira et al, 2014;Shiotsuki et al, 2014;Valerio et al, 2015). Therefore, the phenotype of these traits in this sheep population exhibited additive genetic variance, and are good indicators for selection.…”
Section: (Co)variance Components and Genetic Parametersmentioning
confidence: 52%
See 1 more Smart Citation